Molecular dynamics simulations on human fibulin-4 mutants D203A and E126K reveal conformational changes in EGF domains potentially responsible for enhanced protease lability and impaired extracellular matrix assembly - Sasaki, Takako; von der Mark, Klaus; Lanig, Harald (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2019)
Fibulin-4 is a 50 kDa glycoprotein of elastic fibers and plays an important role in development and function of elastic tissues. Fibulin-4 consists of a tandem array of five calcium-binding epidermal growth factor-like modules flanked by N- and C-terminal domains. Mutations in the human fibulin-4 gene EFEMP2 have been identified in patients affected with various arteriopathies including aneurysm, arterial tortuosity, or stenosis, but the molecular basis of most genotype-phenotype correlations is unknown. Here we present biochemical and computer modelling approaches designed to gain further insight into changes in structure and function of two fibulin-4 mutations (E126K and D203A), which are potentially involved in Ca2+ binding in the EGF2 and EGF4 domain, respectively. Using recombinantly produced fibulin-4 mutant and wild type proteins we show that both mutations introduced additional protease cleavage sites, impaired extracellular assembly into fibers, and affected binding to to fibrillin-1, latent TGF-β-binding proteins, and the lysyl oxidase LOXL2. Molecular dynamics studies indicated that the E126K and D203A mutations do not necessarily result in a direct loss of the complexed Ca2+ ion after 500 ns simulation time, but in significantly enhanced fluctuations within the connecting loop between EGF3 and EGF4 domains and other conformational changes. In contrast, intentionally removing Ca2+ from EGF4 (D203A ΔCa) predicted dramatic changes in the protein structure. These results may explain the changes in protease cleavage sites, reduced secretion and impaired extracellular assembly of the E126K and D203A fibulin-4 mutants and provide further insight into understanding the molecular basis of the associated clinical phenotype
Keywords: Extracellular matrix protein; Mutation; Matrix assembly; Computer simulation; Fibulin-4